New insights into the intercalation chemistry of Al(OH)3. - Williams, G; Moorhouse, S; Prior, T; Fogg, A; Rees, N; O'Hare, D (2011)
This paper reports a number of recent developments in the intercalation chemistry of Al(OH)(3). From Rietveld refinement and solid-state NMR, it has been possible to develop a structural model for the recently reported [M(II)Al(4)(OH)(12)](NO(3))(2)·yH(2)O family of layered double hydroxides (LDHs). The M(2+) cations occupy half of the octahedral holes in the Al(OH)(3) layers, and it is thought that there is complete ordering of the metal ions while the interlayer nitrate anions are highly disordered. Filling the remainder of the octahedral holes in the layers proved impossible. While the intercalation of Li salts into Al(OH)(3) is facile, it was found that the intercalation of M(II) salts is much more capricious. Only with Co, Ni, Cu, and Zn nitrates and Zn sulfate were phase-pure LDHs produced. In other cases, there is either no reaction or a phase believed to be an LDH forms concomitantly with impurity phases. Reacting Al(OH)(3) with mixtures of M(II) salts can lead to the production of three-metal M(II)-M(II)'-Al LDHs, but it is necessary to control precisely the starting ratios of the two M(II) salts in the reaction gel because Al(OH)(3) displays selective intercalation of M nitrate (Li > Ni > Co ≈ Zn). The three-metal M(II)-M(II)'-Al LDHs exhibit facile ion exchange intercalation, which has been investigated in the first energy dispersive X-ray diffraction study of a chemical reaction system performed on Beamline I12 of the Diamond Light Source.